Biochemical and molecular characterization of a new heme peroxidase from Aspergillus niger CTM10002, and its application in textile reactive dye decolorization. (October 2022) - Hamdi, Sondes; Allala, Fawzi; Mechri, Sondes; Bouacem, Khelifa; Rekik, Hatem; Hacene, Hocine; Jaouadi, Bassem; Le Roes-Hill, Marilize; Zaraî Jaouadi, Nadia
Abstract: The presence of textile dyes in wastewater of textile factories represents a major environmental problem, threatening aquatic life. The decolorisation and degradation of harmful textile-dyes therefore remains a key field of research. In this study, a novel extracellular heme-manganese-peroxidase (30 kDa-MnP AN30) produced by Aspergillus niger strain CTM10002, a strain which was isolated from contaminated-wastewater of a nitrogen-phosphate-potash (NPK) chemical company in Sfax (Tunisia), was evaluated for its efficiency in the decolorization of different textile-dyes. Purification yield reached 60%, with a specific activity of 372 U/mg and Reinheitzahl (RZ) value of 2.8 under the optimal conditions of 40 °C and pH 5. The MnP AN30 NH2 -terminal sequence was characterized by a high degree of similarity with those of other fungal-peroxidases. The mnp AN30 gene was cloned, sequenced, and expressed in Escherichia coli strain BL21(DE3)pLysS . Biochemical properties of the recombinant enzyme (rMnP AN30) were similar to those of the native one. Interestingly, molecular modeling and docking of MnP AN30 heme binding site revealed the involvement of 19 amino acid residues in substrate binding. More interestingly, MnP AN30 is capable of decolorizing textile dyes with higher decolorization efficiency than MnP TC55 from Trametes pubescens strain i8. Accordingly, these properties showed the potential candidacy of MnP AN30 to be used in biological treatment and decolorization of synthetic textile dyes. Graphical Abstract: Flowchart of the study overview ga1 Highlights: New 30 kDa heme manganese peroxidase from A. niger CTM10002 was purified (MnP AN30). Optimum pH and temperature values for activity were pH 5 and 40 °C, respectively. The mnp AN30 gene was cloned, sequenced, and expressed in E. coli BL21(DE3)pLysS. Docking data provided insight into the involvement of 19 amino acid residues in the substrate binding. MnP AN30 is considered a promising candidate for textile dyes biological treatment and decolorization.